FABRICATION AND CHARACTERIZATION OF THE MECHANICAL PROPERTIES OF COPPER MATRIX COMPOSITE REINFORCED BY GRAPHENE – CARBON NANOTUBE HYBRID MATERIALS - Dinh Phuong, Doan; Bao Trung, Tran; Ngoc Minh, Phan; Van Trinh, Pham (Vietnam Journal of Science and Technology, 2025)
In this work, graphene-carbon nanotube/copper (Gr-CNT/Cu) composites were fabricated by using spark plasma sintering (SPS) technique. The effect of Gr-CNT hybrid material on the microstructure, mechanical properties and wear behavior of the composites was investigated. The obtained result showed that the Gr-CNT hybrid material was uniformly dispersed on the surface of Cu particles. The relative density of the fabricated Gr-CNT/Cu composite was higher 98%. The composite exhibited enhanced hardness and tensile strength relative to pure copper. The enhancement in hardness and tensile strength was attributed to the incorporation of Gr-CNT hybrid material. Furthermore, the friction coefficient and wear rate of the composite decreased by 43% and 50%, respectively, in comparison to pure Cu. The reduction in the friction coefficient of the composite indicated the excellent wear resistance of the Gr-CNT hybrid material within the Cu matrix.